Current Trends of Exercise Programs for Improving Cognitive Function in Older Adults - Jae-Hyun Lee; Wooyeon Jo; Jaeho Jin; Yaxiong Zheng; Soyoon Lee; Se-Yeon Jang; Minseo Kim; Young-Jin Moon; Hye Gwang Jeong; Sang Ki Lee (운동과학)
PURPOSE Limited studies have analyzed exercise protocols for cognitive improvement in older adults. Therefore, we closely examined the composition, content, and operation methods of these exercise programs to identify current trends. METHODS We searched the Web of Science, PubMed, and Google Scholar databases for studies published between 2019 and 2024. The search terms used included “older adults”, “cognitive function”, “mild cognitive impairment”, “dementia”, “exercise”, “physical activity”, and other related terms, in both Korean and English. RESULTS Aerobic exercises primarily comprised step-based exercises (walking and stepping) and dance routines, typically lasting 15-60 minutes per session, 1-3 times per week for 6-24 weeks, regardless of the individual's cognitive level. Assistant instructors often participated, and in cases of severe cognitive impairment, patients’ caregivers also participated. Resistance exercises were most often performed using body weight and elastic bands, along with other tools and equipment, such as balls, water bottles, or specialized equipment. The exercises commonly involved 8-12 repetitions, 2-3 sets, with 1-minute rest between sets. Several programs included functional exercises to improve daily living performance. Other activities that were incorporated into the exercise programs included exergames and balance, mind-body, peripheral, and eye exercises. CONCLUSIONS Recent cognitive exercise programs for older adults typically last three months and use a variety of tools or digital technologies within the scope of older adult exercise guidelines. Exercises for people with severe cognitive impairment tend to be more individualized, gradual, and flexible in their approach.